Coronary Angiographic Profile in Patients with Conduction System Disorder Requiring Permanent Cardiac Pacing - Majumder, AAS; Ali, MA; Rashid, MTBA (Cardiovascular Journal, 2012)
Background: The association between conduction disturbances and atherosclerotic coronary artery disease has been investigated in a few small studies in the early 1970s and the study result was inconclusive. Thereafter some investigators found in their separate study that a group of patients with conduction disturbances that required permanent pacemaker who had coronary atherosclerotic disease that might be responsible for conduction disturbances. Method: 40 consecutive patients that required permanent pacemaker and 40 control patients were investigated. The coronary angiographic study was performed in both groups which included classification of pathological coronary anatomy, qualitative assessment of flow and stenosis severity. Results: The location of the lesions was found significantly different between two groups. 14 patients(35%) of 40 study patients had type IV lesion, whereas only 2 patients(5%) of 40 control patients had type IV lesion (p=0.001). Flow quality was found poor in more patients in study group specially that had type IV lesion. Severity of the lesions in the LAD & RCA was found identical in both groups. Conclusion: It may be concluded that the location of the lesions rather than diffuse coronary atherosclerosis might be responsible for a subset of patients with conduction disturbances that required permanent pacemaker. Key words: Conduction disturbances; Permanent pacemaker; Coronary angiogram; Type of coronary artery lesion. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9392 Cardiovasc. J. 2011; 4(1): 61-66